Strategi Promosi dan Pemasaran Dinas Pariwisata untuk Meningkatkan Kunjungan Wisatawan di Kabupaten Karimun - Mei Shinta Sihombing; Yudhanto Satyagraha Adiputra; Uly Sophia (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The promotion and marketing efforts by the Tourism Office of Karimun Regency aim to introduce and effectively promote local tourist destinations to both domestic and international visitors. According to a previous study by Andriani (2020), the development of tourist sites in Karimun Regency has not yet been fully realized by the local government. This research aims to reexamine and optimize Karimun's tourism potential through programs implemented by the Tourism Office, supporting local economic changes. This study uses a descriptive method with a qualitative approach, gathering data through interviews with informants, field notes, and relevant official documents. It focuses on examining the promotion strategies carried out by the Tourism Office to increase tourist visits. Based on Kooten's theory, there are four strategic indicators: organizational strategy, program organization, resource support strategy, and institutional strategy. The research results show that all strategic indicators have been implemented well in accordance with funding from the center, providing a positive impact on the development of tourist destinations and increasing the number of tourists who come to visit tourist attractions in Karimun district. However, if funding is not in accordance with the annual plan, the program that has been prepared by the marketing and promotion division will have an impact, hampering efforts to increase tourist visits from both inside and outside Karimun Regency.